The Immunologic Effect of Early Intravenous Two and Four Gram Bolus Dosing of Tranexamic Acid Compared to Placebo in Patients With Severe Traumatic Bleeding (TAMPITI): A Randomized, Double-Blind, Placebo-Controlled, Single-Center Trial - Spinella, Philip C.; Thomas, Kimberly A.; Turnbull, Isaiah R.; Fuchs, Anja; Bochicchio, Kelly; Schuerer, Douglas; Reese, Stacey; Coleoglou Centeno, Adrian A.; Horn, Christopher B.; Baty, Jack; Shea, Susan M.; Meledeo, M. Adam; et al. (Frontiers in Immunology, 2020)
Background The hemostatic properties of tranexamic acid (TXA) are well described, but the immunological effects of TXA administration after traumatic injury have not been thoroughly examined. We hypothesized TXA would reduce monocyte activation in bleeding trauma patients with severe injury. Methods This was a single center, double-blinded, randomized controlled trial comparing placebo to a 2 gram or 4 gram intravenous TXA bolus dose in trauma patients with severe injury. Fifty patients were randomized into each study group. The primary outcome was a reduction in monocyte activation as measured by human leukocyte antigen-DR isotype (HLA-DR) expression on monocytes 72 hours after TXA administration. Secondary outcomes included kinetic assessment of immune and hemostatic phenotypes within the 72 hour window post-TXA administration. Results The trial occurred between March 2016 and September 2017, when data collection ended. 149 patients were analyzed (placebo, n=50; 2 gram TXA, n=49; 4 gram TXA, n=50). The fold change in HLA-DR expression on monocytes (reported as median (Q1-Q3)) from pre-TXA to 72 hours post-TXA was similar between placebo (0.61 (0.51-0.82)), 2 gram TXA (0.57 (0.47-0.75)), and 4 gram TXA (0.57 (0.44-0.89)) study groups (p=0.82). Neutrophil CD62L expression was reduced in the 4 gram TXA group (fold change: 0.73 (0.63-0.97)) compared to the placebo group (0.97 (0.78-1.10)) at 24 hours post-TXA (p=0.034). The fold decrease in plasma IL-6 was significantly less in the 4 gram TXA group (1.36 (0.87-2.42)) compared to the placebo group (0.46 (0.19-1.69)) at 72 hours post-TXA (p = 0.028). There were no differences in frequencies of myeloid or lymphoid populations or in classical complement activation at any of the study time points. Conclusions In trauma patients with severe injury, 4 gram intravenous bolus dosing of TXA has minimal immunomodulatory effects with respect to leukocyte phenotypes and circulating cytokine levels. Trial Registration ClinicalTrials.gov identifier: NCT02535949 Funding US Department of Defense, US Army Medical Research and Materiel Command Award W81XWH-14-1-0373; Department of Surgery, Washington University in St Louis, St Louis, MO; Department of Pediatrics, Washington University in St Louis, St Louis, MO; US Army Institute of Surgical Research, Joint Base San Antonio-Fort Sam Houston, TX.